2018
DOI: 10.1007/s00261-018-1681-2
|View full text |Cite
|
Sign up to set email alerts
|

MRI of pancreatic ductal adenocarcinoma: texture analysis of T2-weighted images for predicting long-term outcome

Abstract: Tumor size was a significant predictive factor for RFS and OS in PDAC patients. Although entropy with medium texture analysis was significantly associated with OS, there were also limitations in the texture analysis; thus, further study is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…This leads to mutual advantages of high and low level SIFT features during the decoding. The mean dice value for PDAC mass segmentation using (1) Attention U-Net + LBP, (2) Attention U-Net + SIFT_1 + LBP, (3) Attention U-Net + SIFT_2 + LBP, (4) Attention U-Net + SIFT_4 + LBP and (5) Attention U-Net + SIFT_8 + LBP were 0.54, 0.55, 0.53, 0.58 and 0.55 respectively. SIFT_ n , means that the SIFT map with step size of n is added to the corresponding layer in the decoder path.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to mutual advantages of high and low level SIFT features during the decoding. The mean dice value for PDAC mass segmentation using (1) Attention U-Net + LBP, (2) Attention U-Net + SIFT_1 + LBP, (3) Attention U-Net + SIFT_2 + LBP, (4) Attention U-Net + SIFT_4 + LBP and (5) Attention U-Net + SIFT_8 + LBP were 0.54, 0.55, 0.53, 0.58 and 0.55 respectively. SIFT_ n , means that the SIFT map with step size of n is added to the corresponding layer in the decoder path.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic potential of quantitative imaging features for PDAC in the analysis was reported by several studies [29][30][31][32]. In an earlier study, twenty-six PDAC subjects were studied to identify clinical or textural features associated with survival by comparing the change between pre-and post-treatment 18 F-FDG-PET/CT images [32].…”
Section: Discussionmentioning
confidence: 99%
“…The identified features were provided as a feasible approach for evaluation and prediction of clinical outcomes. A recent study focused on T2-weighted MRI images to assess the association between radiomics features and pathological aggressiveness or clinical outcomes of 18.5 months after pancreatectomy procedure [30]. As tumor size was observed as a significant element to predict recurrence-free and overall survival, entropy with medium texture analysis was associated with the survival of PDAC patients.…”
Section: Discussionmentioning
confidence: 99%
“…CTTA has been correlated with pathological results in a few studies (85,86) and shown to correlate with the outcomes of pancreatic adenocarcinoma patients. Choi et al (87) have retrospectively evaluated 66 pancreatic adenocarcinoma patients who had pre-operative 3T MRI scans and showed that tumor size was a significant predictive factor for both recurrence free and overall survival. However, other TA parameters which showed statistical significance to predict recurrence free and overall survival according to univariate analysis did not remain significant after multivariate analysis.…”
Section: Mrta For Other Abdominal and Pelvic Conditionsmentioning
confidence: 99%